Protein C Activity in Dogs: Adaptation of a Commercial Human Colorimetric Assay and Evaluation of Effects of Storage Time and Temperature - Michael M. Fry; Karl R. Snyder; Karen M. Tobias; Baye G. Williamson; G. Ann Reed (Veterinary Medicine International)
Objectives of this study were to adapt a commercial human protein C (PC) colorimetric assay for use in dogs and to investigate effects of various storage conditions. The human assay was modified by using pooled canine plasma for calibration and by increasing the activation time. PC activity was measured in fresh canine plasma and in plasma stored under various conditions. PC activity of some stored samples was significantly different from that of fresh plasma; however, differences were small. No difference was detected in samples stored under similar conditions but analyzed in different laboratories using similar methodology. Results of this study indicate that the human colorimetric assay is suitable for canine samples if pooled canine plasma is used for calibration, that Clinical and Laboratory Standards Institute sample storage guidelines developed for testing in humans are appropriate for dogs, and that comparisons of results from laboratories using similar methodology are legitimate.